Treatment of Soft Tissue and Bony Spinal Stenosis by a Visualized Endoscopic Transforaminal Technique Under Local Anesthesia - Anthony Yeung; Andrew Roberts; Lifan Zhu; Lei Qi; Jun Zhang; Kai-Uwe Lewandrowski (Neurospine, 2019)
Objective To analyze long-term clinical outcomes of endoscopic transforaminal foraminoplasty for foraminal stenosis. Methods Long-term 5-year MacNab outcomes, visual analogue scale (VAS) scores, complications, and unintended aftercare were analyzed in a series of 86 patients who underwent endoscopic transforaminal foraminoplasty for foraminal stenosis. Results At minimum 5-year follow-up, excellent results according to the MacNab criteria were obtained in 32 patients (37.2%), Good in 40 (46.5%), fair in 11 (12.8%), and poor in 3 (3.5%), respectively. The mean preoperative VAS was 6.15. The mean postoperative and last follow-up VAS was 3.44. Both postoperative VAS and last follow-up VAS were statistically reduced at a significance level of p<0.0001. Postoperative dysesthesia occurred in 9 patients. Another 9 patients had recurrent disc herniations (10.5%). Failure to cure with persistent pain occurred in 3 patients. Two patients developed pain postoperatively stemming from a different level. One patient experienced a postoperative hematoma which ultimately was inconsequential and did not require any additional surgery. Only 3 patients opted for revision endoscopic discectomy and another 2 for revision fusion surgery. Conclusion Patients with symptomatic foraminal stenosis may be treated successfully with early transforaminal endoscopic decompression while maintaining favorable long-term outcomes without the need for fusion in the vast majority of patients.